Deskripsi Intuisi Siswa Berdasarkan Tingkat IQ Dalam Penyelesaian Masalah Matematika Pada Materi Geometri Kelas VII SMPN 6 Kediri - Anjayani, Vinansia Yulian (Prosiding SI MaNIs (Seminar Nasional Integrasi Matematika dan Nilai-Nilai Islami), 2017)
Intuition is one way of thinking in math problems. Conscious or not every person often uses the intuition they have in solving a problem. One of them is solving mathematical problems in geometry material. In solving math problems can also be influenced by the level of IQ that students have. The purpose of this study was to describe Student Intuition with different IQ level of Class VII on Geometry Material. This research is a descriptive qualitative research type. A total of 3 Grade VII students were selected as samples at different IQ levels. Then classified into 3 groups of high, medium and low. After that the three samples will be given a geometry test whose indicators are adjusted with intuition. Then Through the in-depth interview will be obtained a description of student intuition in solving geometry problems. Along with the interview the researcher will observe the student activity. Then the data obtained will be analyzed. So the instruments in this study are IQ tests, questions and interview sheets.